2022
DOI: 10.3389/fsurg.2022.971030
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of lymph node ratio in breast cancer patients received neoadjuvant chemotherapy: A dose-response meta-analysis

Abstract: BackgroundAs neoadjuvant chemotherapy is widely used in breast cancer patients, the lymph node ratio has not been fully validated as a prognostic indicator of breast cancer received neoadjuvant chemotherapy. This study was conducted to investigate the prognostic value of lymph node ratio in breast cancer patients received neoadjuvant chemotherapy.MethodsSystematic searches were performed in the PubMed, Embase, and Cochrane Library databases until 15 December 2021 for studies on the association between lymph no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In these types of cancer, LNs are the first sites to be invaded. Indeed, the presence or absence of cancer cells in the first draining LN (also known as sentinel LN) has been recognized as a prognostic factor in several human cancers, often being even more reliable than already established clinical parameters such as tumor size or histological grade 100 , 101 .…”
Section: Role Of Lymphatic Vessels In Pathologymentioning
confidence: 99%
“…In these types of cancer, LNs are the first sites to be invaded. Indeed, the presence or absence of cancer cells in the first draining LN (also known as sentinel LN) has been recognized as a prognostic factor in several human cancers, often being even more reliable than already established clinical parameters such as tumor size or histological grade 100 , 101 .…”
Section: Role Of Lymphatic Vessels In Pathologymentioning
confidence: 99%
“…[8][9][10][11] Furthermore, previous studies have shown that factors related to a shorter disease-free survival (DFS) include lymph node involvement, tumors larger than 2 cm, and triple negative hormone receptor status. [12][13][14] Moreover, therapeutic modalities for breast cancer may also significantly affect DFS. Bundred et al found that involved or close pathological margins after breast conserving surgery for early-stage invasive breast cancer were associated with increased distant recurrence and local recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…This survival relationship suggests better reliability of the lymph node ratio. An abundant literature showed the advantage of a ratio-based classification over conventional numbers in nonmetastatic disease in various conditions (9,10). Considering that non-optimal categorization of lymph nodes might have confounded prognostic groups in dnMBC, the present study sought to evaluate whether nodal ratios provide prognostic information in dnMBC.…”
mentioning
confidence: 99%